Urgensi Rancangan Undang-Undang Perampasan Aset dalam Optimalisasi Pengembalian Hasil Korupsi di Indonesia - Andari Rizky Aria Putra; Trini Handayani; Aji Mulyana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The development of corruption nowadays is accompanied by other crimes related to hide assets from corruption and one way of it is by money laundering mechanism. The mechanism of it is contained in the Criminal Code, Criminal Procedure Code, Law No. 20/2001 jo. Law No. 31/1999 concerning the Eradication of Corruption and Law No. 8/2010 concerning Prevention and Eradication of the Crime of Money Laundering. There are also international legal instruments adopted to strengthen efforts to seize assets from criminal acts of corruption, such as UNCAC which was ratified by the Government of Indonesia into Law Number 7/2006 concerning Ratification of the UNCAC on April 18, 2006. Indonesia needs a regulation that has stronger legal force and has a special mechanism regarding the mechanism for the confiscation of assets and assets that are suspected of being obtained as a result of corruption. It can be suggested to the Government and the legislature to encourage the discussion and passing of the asset confiscation bill’s immediately.